Perception of undergraduates on their language competence based on english language national examination results - Abdullah, M.R.T.L. (Universiti Putra Malaysia, 2015)
This study aims to investigate the perception of undergraduate students on their language competence in meeting the requirement to take English for Specific purpose course at tertiary level. The investigation was conducted using survey questionnaire on 250 undergraduate students to obtain their perception on their actual language competence based on the national language examination results as preparatory to register for Professional & Communication skills course (English for Specific Purpose subject). The findings indicated that despite obtaining excellent grade in English Language, a majority of them perceived lack in language competence to sit for the university language course. About 42.3 (n=92) of the respondents perceived that their results over rated their actual oral skills, while 48.2 (n=105) of the respondents perceived that their results matched their actual writing skills. The findings could implicate the reliability of the national examination to be used as benchmarking criteria in accepting students in universities. The findings could also motivate the Ministry of Education in improving the method of language assessment to give equivalent weightage to all language skills to not heavily focusing on reading or writing skills. Â© Universiti Putra Malaysia Press.